Cauliflower-like resin microspheres with tuneable surface roughness as solid-phase extraction adsorbent for efficient extraction and determination of plant growth regulators in cucumbers. (15th October 2019) - Wang, Mingwei; Nie, Hailiang; Han, Dandan; Qiao, Xiaoqiang; Yan, Hongyuan; Shen, Shigang
Highlights: A new cauliflower-like PGRMs was synthesized using a green strategy. The surface roughness morphology of the PGRMs can be tuned. Glyoxylic acid instead of toxic formaldehyde was used as crosslinker. The adsorption process of PGRMs was monolayer chemical adsorption. A new PGRMs-SPE method was developed to extract PGRs from cucumbers. Abstract: New cauliflower-like phloroglucinol-glyoxylic acid resin microspheres (PGRMs) with controllable diameters and tuneable surface roughness were prepared using a one-step environmentally-friendly method without a catalyst. The PGRMs obtained exhibited a rough surface, narrow size distribution, and excellent adsorption capacity for polar compounds. The PGRMs were employed as an adsorbent for solid phase extraction (SPE) of kinetin (KT) and 6-benzyladenine (6-BA) in cucumbers and demonstrated better extraction recoveries and purification efficiency than phloroglucin-formaldehyde resin and common commercial adsorbents. Our PGRMs–SPE–HPLC method showed good linearity (r ≥ 0.9997) ranging from 0.04 to 4.00 μg/g for KT and 6-BA, and recoveries at three spiked concentration ranged from 77.8% to 104.4% with RSDs ≤ 6.8%. This PGRMs–SPE–HPLC method was applied successfully to determine of KT and 6-BA in cucumbers.